PERAN KELEMBAGAAN DINAS SOSIAL DALAM PENANGANAN MASALAH GELANDANGAN DAN PENGEMIS - Kadullah, Priti Melani; Tui, Fenti Prihatini; Nani, Yakob Noho (Gorontalo State University, 2025)
ABSTRACT This study aims to analyze the institutional role of the Social Affairs Office in addressing the issue of homeless people and beggars in Gorontalo City, focusing on preventive, repressive, and rehabilitative efforts. The approach used is quantitative with a descriptive research type. Data were collected through interviews, observation, and documentation. Data analysis employed the Miles and Huberman model. The results of the study show that: (1) The preventive efforts of the Social Affairs and Community Empowerment Office of Gorontalo City in handling the issue of homelessness and begging are carried out through counseling for vulnerable families, job skills training for poor groups, and mapping of areas prone to homelessness and begging. Collaboration with other agencies such as the Public Order Agency (Satpol PP), Health Department, and religious institutions further strengthens these efforts. (2) The repressive approach is implemented in an integrated manner with Satpol PP and the Police through regular and coordinated operations to control homeless people and beggars. These activities include identification, data collection, legal action against exploiters, and the application of the Regional Regulation on Public Order as the operational basis. (3) Rehabilitative efforts focus on the recovery and social reintegration of homeless people and beggars through various services such as placement in shelters, spiritual guidance, job skills training, and facilitation of entrepreneurship programs. Reintegration with original families and post-rehabilitation monitoring are also key parts of the long-term strategy of the Social Affairs Office. The implementation of these activities also involves cooperation with educational institutions, cooperatives, MSMEs, and BAZNAS to support economic sustainability after rehabilitation. Keyword: Homeless; Beggars; Institutional; Social; Handling ABSTRAK Penelitian ini bertujuan untuk menganalisis peran kelembagaan dinas sosial dalam penanganan masalah gelandangan dan pengemis di Kota Gorontalo yang terdiri atas upaya preventif, upaya represif dan upaya rehabilitatif. Pendekatan yang digunakan yakni kuantitatif dengan jenis penelitian deskriptif. Pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Analisis data menggunakan model Miles dan Huberman. Hasil penelitian ini menunjukan bahwa (1) upaya preventif Dinas Sosial dan Pemberdayaan Masyarakat Kota Gorontalo dalam menangani masalah gelandangan dan pengemis dilakukan melalui penyuluhan kepada keluarga rentan, pelatihan keterampilan kerja bagi kelompok miskin, serta pemetaan wilayah rawan gepeng. Kolaborasi dengan instansi lain, seperti Satpol PP, Dinas Kesehatan, dan lembaga keagamaan turut memperkuat upaya ini. (2) Pendekatan represif Dinas Sosial dan Pemberdayaan Masyarakat dijalankan secara terpadu dengan Satpol PP dan Kepolisian, melalui kegiatan operasi penertiban gepeng yang bersifat rutin dan terkoordinasi. Kegiatan ini mencakup identifikasi, pendataan, dan tindakan hukum terhadap pelaku eksploitasi, serta penerapan Perda Ketertiban Umum sebagai landasan operasional. (3) Upaya rehabilitatif difokuskan pada pemulihan dan reintegrasi sosial gepeng melalui berbagai layanan seperti penempatan di rumah singgah, pembinaan spiritual, pelatihan keterampilan kerja, serta fasilitasi program kewirausahaan. Reintegrasi dengan keluarga asal dan pemantauan pascarehabilitasi juga menjadi bagian penting dalam strategi jangka panjang Dinas Sosial. Pelaksanaan kegiatan ini turut melibatkan kerja sama dengan lembaga pendidikan, koperasi, UMKM, dan BAZNAS guna mendukung keberlanjutan ekonomi pascarehabilitasi. Kata Kunci: Gelandangan; Pengemis; Kelembagaan; Sosial; Penanganan